CGIAR Livestock, Climate and System Resilience Initiative in Kenya: activities, partnerships, and achievements - Shikuku, Kelvin Mashisia (International Livestock Research Institute, 2023)
CGIAR initiative on Livestock and Climate in Kenya: Working closely with key actors to provide knowledge, information and tools needed to make robust evidence-based decisions to reduce food systems emissions.